Profit Decomposition: Analyzing the Pathway from Carbon Dioxide Emission Reduction to Revenues and Costs - Rokhmawati, Andewi (International Journal of Energy Economics and Policy, 2020)
In 2009, the Indonesian Government has introduced regulation on reducing CO2 emission known as ‘energy management’ to follow up its commitment to reduce CO2 emission that was ratified in the Kyoto Protocol. The regulation mandates companies in Indonesia which consumed more than 6,000-tonne of oil equivalent (TOE). The obligation to reduce CO2 emission has an implication to the companies that the company has to implement strategies incorporating an expensive investment. Through investment, the company’s sales are expected to increase and costs are expected to decrease. Several conceptual frameworks have been developed to identify through which pathway CO2 emission reduction can gain profits for companies but a little study (if any) has been done to analyze the pathways of CO2 emission reduction that can improve companies’ profits. This study aims to examine the pathway of CO2 emission reductions to the profits generated by revenues and costs. The purposive sampling method was used to obtain data from 384 companies that consumed 6,000-tonne of oil equivalent (TOE) from 2016-2017 in Indonesia. The multiple regression analysis with Ordinary Least Square was used to analyze their relationship. The results showed that in the case of Indonesia, the CO2 emission reduction can generate profits through both pathways namely revenue improvement and cost-efficiency. The increase in revenues and decrease in cost are due to their ability to meet customers’ interests, the positive responses of stakeholders in compliance with the regulation to reduce CO2 emissions, and the investment of environmentally friendly machinery. Keywords: CO2 emissions; costs; decomposition; profit; revenues. JEL Classifications: Q48; Q51; G3 DOI: https://doi.org/10.32479/ijeep.9346